Pick n Pay’s- drive for food courtesy in South African communities. - Mokale, Reshoketswe (The IIE, 2020)
The aim in research was to shed light on awareness among consumers on the problematic ongoing food wastage. Focussing on South African shores through a healthy meaningful brand. That would better convey the message of consumers changing their lifestyles to accommodate their near future of less wastage and good practice of food waste management. By the accumulation of consumer insight, various ways of transferring information about food management would be localised and user ready for application in the daily lives of consumers. The significance and importance of this report were to indicate practical solutions that can prevent and or minimise the wasting of food throughout the food supply chain from retail to consumer's hands. The reason for the research was to create a useful channel in couching South Africans on manners that food can be saved by them. The vision was to get positive and consistent involvement in communities despite there being no legislation on the management of food. A critical realist study in society was used because the technique is to understand the realities of society inductive reasoning to have liberated the consumer from a vicious lifestyle cycle. It is challenging to market solutions to an issue like this but various worldwide initiatives that are driven correctly have proven to have a dramatic influence on a social and economic crisis like food wastage. The goal here is that when capital is directed to teaching the language that would action change the hypotheses posed that education in this instance awareness can eventually eliminate contradictory phenomena of food wasting and hunger. People are interested in transforming their lives to do better when there is involvement in participating in activities that support that. Pick n Pay is a powerful brand because of its customer values, that it can see the world through the eyes of the consumer. this is a brand that has already had the ball rolling with regards to the food waste phenomena. The brand’s involvement of consumers would be to create a greater impact on society.
Keywords: Consumer awareness; Healthy brand; Meaningful brands; Brand value